2019
DOI: 10.1021/acs.jpcc.9b09721
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitization Ability of 1,7-Phenanthroline Based Bis−BODIPYs: Perplexing Role of Intramolecular Rotation on Photophysical Properties

Abstract: 1,7-Phenanthroline based bis−boron dipyrromethenes (bis−BODIPYs) B1 and B2 obtained via small substitutional changes (−Cl/–SCH3) have been described. The effect of restriction of intramolecular rotation (RIR) in emission enhancement in a viscous solvent (glycerol) has been studied besides the vital role of intermolecular interactions scrutinized by X-ray single-crystal studies. The efficiency of intersystem crossing (ISC) in the generation of singlet oxygen (ΦΔ ∼ 19.2% and 56.7%) by photoirradiation using visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 67 publications
2
15
0
Order By: Relevance
“…Over the course of 7 min under irradiation, tri-BDP underwent an overall 83% decrease of DPBF absorbance compared to its initial absorbance (Figure ). Based on it, the singlet oxygen ( 1 O 2 ) quantum yield (Φ Δ ) was calculated using Rose Bengal as a reference (RB, Φ Δ = 0.80 in methanol), which came out to be ∼71%. , This experiment clearly substantiated the photosensitization and singlet oxygen ( 1 O 2 ) generation ability of tri-BDP . Furthermore, it was also observed that during the course of experiment, photobleaching of tri-BDP does not occur, and thus it may be concluded that it acts as a good photosensitizer. ,, …”
Section: Resultsmentioning
confidence: 64%
See 3 more Smart Citations
“…Over the course of 7 min under irradiation, tri-BDP underwent an overall 83% decrease of DPBF absorbance compared to its initial absorbance (Figure ). Based on it, the singlet oxygen ( 1 O 2 ) quantum yield (Φ Δ ) was calculated using Rose Bengal as a reference (RB, Φ Δ = 0.80 in methanol), which came out to be ∼71%. , This experiment clearly substantiated the photosensitization and singlet oxygen ( 1 O 2 ) generation ability of tri-BDP . Furthermore, it was also observed that during the course of experiment, photobleaching of tri-BDP does not occur, and thus it may be concluded that it acts as a good photosensitizer. ,, …”
Section: Resultsmentioning
confidence: 64%
“…A constant decrease in absorption at 410–415 nm (characteristic peak due to DPBF) clearly indicated 1 O 2 generation. The singlet oxygen ( 1 O 2 ) causes the oxidative degradation of DPBF, leading to a gradual decrease in the absorption at 410–415 nm. ,, Further, absorption intensity at ∼415 nm has been plotted against time intervals, which showed a linear relationship (with a slope value of 55) (Figure ). This observation suggested efficient photogeneration of 1 O 2 due to the photosensitization ability of tri-BDP .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other catalysts used in the photo-oxidation of 1,5-dihydroxynaphthalene to Juglone (85: R 1 = R 2 = R 5 = H, R 4 = OH) were two perylenebisimide- [60]fullerene systems dissolved in CH2Cl2/MeOH (9:1) (86a,b) (Figure 23) [183], although only the quantum yield of the transformation was reported. In addition, a mixture of two 1,7-phenanthroline based bis-BODIPYs with Cl-or SMesubstituents (87a,b) [184] and two BODIPY-carbazole derivatives (88a,b) [185] photocatalyzed the same oxidation of 1,5-dihydroxynaphthalene to Juglone (85: R 1 = R 2 = R 5 = H, R 4 = OH), only reporting the obtained quantum yield in the first case (Figure 24). Furthermore, methylene blue 1 has been employed in the photo-oxidation of different phenols and naphthols to quinones or naphthoquinones under continuous-flow conditions, obtaining good results [186].…”
Section: Ohmentioning
confidence: 99%